Recursion Operator and Local and Nonlocal Symmetries of a New Modified KdV Equation - Qian Suping; Li Xin (Advances in Mathematical Physics)
The recursion operator of a new modified KdV equation and its inverse are explicitly given. Acting the recursion operator and its inverse on the trivial symmetry 0 related to the identity transformation, the infinitely many local and nonlocal symmetries are obtained. Using a closed finite dimensional symmetry algebra with both local and nonlocal symmetries of the original model, some symmetry reductions and exact solutions are found.